Motivasi atas Sikap Mahasiswa Generasi Milenial terhadap Literasi Digital di Prodi Kesmas STIKES Syedza Saintika - Amna, Fitra Afrida; Saibi, Elvina A; Wahyuni, Uli (Universitas Batanghari Jambi, 2024)
During the industrial revolution 4.0, the millennial generation should need to cultivate adequate digital literacy. The era of the industrial revolution 4.0 towards industry 5.0 which is characterized by super smart digital technology requires literacy that is not just literacy in the form of reading, writing, and counting (calistung). Equipping digital literacy to the millennial generation can encourage the realization of a superior and competitive generation in the future for academic purposes (digital literacy for academic purposes). The purpose of this study is to reveal the motivation for the attitude of using digital literacy of millennial generation students in terms of social media ownership, and the use of e-learning in digital-based learning. The research was conducted by quantitative descriptive method. Data is collected by giving questionnaires through google forms along with the reasons for choosing the selected answers. The data in this study were analyzed descriptively which was presented in the form of a bar chart to illustrate the motivation for the attitude of using digital literacy in students of the health study program at STIKes Syedza Saintika. The results showed that millennial generation students have high motivation towards digital literacy, driven by awareness of the importance, demands of work, positive impact on learning, motivation to innovate, and self-empowerment. Higher education needs to pay attention to the results of this research to develop strategies that can further motivate students in developing their digital literacy to face the challenges of an increasingly digitalized future. Research can be directly useful in improving the digital literacy of millennial generation students, for academic purposes (digital literacy for academic purposes), and strengthening the role of universities as promoters of the digital literacy movement in Indonesia.